Field Emission from Carbon Nanotube/Tin Composite - 赵波 张亚非 (Shanghai jiao tong da xue xue bao, 2009)
Powder metallurgy was used to fabricate carbon nanotube （CNT） field emission cathodes. CNTs and tin （Sn） powder were blended, compacted and sintered. After polishing and etching, CNTs were exposed and protruded from the metal surface. CNTs were embedded into the Sn matrix, which acted as stable field emitters. The J--E curves show excellent field emission properties, such as low turn-on field of 2.8 V/μm, high emission current density and good current stability.